The Ratification of the 1932 Accord Relating to the Interpretation of Section 9 of the Concordat Concluded between the Holy See and the Romanian Government on 10 May 1927 - HOLLÓ, László (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2021)
Following the Treaty of Trianon, the situation of the Catholic Church oper-ating on the territory of the Kingdom of Romania was regularized within a con-cordat agreement concluded in 1927 between the Romanian Government and the Holy See as interested parties. Since due to the compromises Section 9 of the Concordat, addressing the le-gal situation of the church, became meaningful ─ a development that parties opposing the Concordat exploited –, the contracting parties agreed on a detailed explanation under an accord drafted in the early 1930s. Our study presents the thriller-like antecedents and aftermath of the Accord, signed on 30 May 1932 between the contracting parties, relating to the inter-pretation of Section 9 of the Concordat concluded between the Holy See and the Romanian Government on 10 May 1927. The successive, short-lived Ro-manian governments could not give effect to the agreement due to the national-ist propaganda heavily present in the media. Abuses arising from the various in-terpretations eventually led to the appearance of the Accord in the form a de-cree-law on 2 May 1940.